Repressive Effect of Sp1 on the C/EBPα Gene Promoter: Role in Adipocyte Differentiation - Tang, Qi-Qun (American Society for Microbiology, 1999)
Expression of C/EBPα is required for differentiation of 3T3-L1 preadipocytes into adipocytes. Previous investigations indicated that transcription of the C/EBPα gene is sequentially activated during differentiation, initially by C/EBPβ and C/EBPδ and later by C/EBPα (autoactivation). These events are mediated by a C/EBP regulatory element in the promoter of the C/EBPα gene. This article presents evidence that members of the Sp family, notably Sp1, act repressively on the C/EBPα promoter prior to the induction of differentiation. Sp1 was shown to bind to a GC box at the 5′ end of the C/EBP regulatory element in the C/EBPα promoter and, in so doing, to competitively prevent binding to and transactivation of the promoter by the C/EBPs. One of the differentiation inducers methylisobutylxanthine (a cAMP phosphodiesterase inhibitor) or Forskolin, both of which increase the cellular cAMP level, causes down-regulation of Sp1. This decrease in Sp1 level early in the differentiation program appears to facilitate access of C/EBPβ and/or C/EBPδ to the C/EBP regulatory element and, thereby, derepression of the C/EBPα gene.